(untitled) (Research, Society and Development, 2022)
Fingerprints are one of the most used biometrics to distinguish persons. This fact is based on important characteristics that they present: stability after full development, easy classification of design patterns, noninvasive enrollment, and uniqueness throughout an individual’s lifetime. In this study, the ridge density from three different areas - ulnar, radial, and proximal - of the ten fingerprints of 100 Brazilian men and 100 women were measured and statistically analyzed. The goal was to verify if these characteristics depended on sex in the interest of distinguishing it categorically. Similar density patterns were found for the ulnar and radial areas, which allowed them to be represented indistinctly through the ridge density for distal region. Significant variability was found between the distal and proximal regions. In both, women showed greater ridge density. In some cases, men and women have statistically significant differences in their hands, fingers, and fundamental patterns of fingerprints. From the distal and proximal ridge density thresholds for sexual discrimination were developed in cases of human identification in Brazil.